2019
DOI: 10.1021/acscatal.8b04575
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Selectivity in Flavin-Dependent Monooxygenase-Catalyzed Oxidative Dearomatization

Abstract: Biocatalytic reactions embody many features of ideal chemical transformations, including the potential for impeccable selectivity, high catalytic efficiency, mild reaction conditions and the use of environmentally benign reagents. These advantages have created a demand for biocatalysts that expand the portfolio of complexity-generating reactions available to synthetic chemists. However, the tradeoff that often exists between the substrate scope of a biocatalyst and its selectivity limits the application of enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 46 publications
(105 reference statements)
1
46
1
Order By: Relevance
“…In contrast, these conserved residues switch positions in biocatalysts that afford products with the S -configuration. We previously demonstrated that a two-point coordination of the phenolate substrate by Tyr237 and an arginine residue is critical for positioning the substrate within the active site in the R -selective enzyme, TropB. , To probe the role of Tyr118 in the stereoselectivity provided by AfoD, the AfoD Y118F variant was generated. AfoD Y118F was reacted with resorcinol S9 to afford dearomatized product in 53:47 ( S : R ) er (Figure S16).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, these conserved residues switch positions in biocatalysts that afford products with the S -configuration. We previously demonstrated that a two-point coordination of the phenolate substrate by Tyr237 and an arginine residue is critical for positioning the substrate within the active site in the R -selective enzyme, TropB. , To probe the role of Tyr118 in the stereoselectivity provided by AfoD, the AfoD Y118F variant was generated. AfoD Y118F was reacted with resorcinol S9 to afford dearomatized product in 53:47 ( S : R ) er (Figure S16).…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies suggested two key active site residues are crucial in controlling the stereochemical outcome of the dearomatization reaction known to these proteins. 36 , 60 Though this does highlight a potential drawback of using SSNs in this way, the tool did ultimately demonstrate its utility in identifying other catalytically active proteins with desired activity. Work is currently underway to further characterize these enzymes in hopes of expanding our library of biocatalysts.…”
Section: Accessibility Of Biocatalysis To Synthetic Chemistsmentioning
confidence: 99%
“…Our 19 F NMR studies demonstrate that the pK a of substrate is depressed in both a single-component and a two-component flavoprotein hydroxylase, supporting deprotonation of the phenol group as a general mechanism of substrate activation for electrophilic attack among these enzymes. Several one-component oxygenases were known to bind substrate in phenolate form (30,31,33,34), but we now place this on quantitative footing, demonstrating 9.1 and 14 kJ/mol stabilization of substrate phenolate consistent with electrostatic or hydrogen bonding mechanisms.…”
Section: Discussionmentioning
confidence: 69%